Perancangan Sistem Informasi Jurnal Mengajar Dosen Berbasis Web Pada Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pendidikan Muhammadiyah Sorong - Firman Firman; Novita Wulandari; Acep Irawan (Universitas Pendidikan Muhammadiyah Sorong, 2020)
The lecturer teaching journal is a device that must be provided by the lecturer after teaching. From the lecturer's teaching jural, it can be known data such as lecture material, courses, meetings, days, times, dates and even the number of students either present or permission and absenteeism. With the development of technology makes people think to be able to work more efficiently. One of them is making a conventional system into a computerized system. For this reason, in the design of a teaching journal information system for lecturers using the R&D (research and development) method and the waterfall model, by utilizing web facilities connected to the internet, the aim is to fill lecturer teaching journals efficiently.In this study a web-based information system was designed using DreamWeaver CS6 and XAMPP 3.2.2. Journal information system testing for teaching lecturers uses blackbox, small scale and large scale testing. With this system, it can make it easier to fill teaching journals of lecturers at the PTI Study Program, Faculty of Teacher Training and Education, Unimuda Sorong From the results of research that has been carried out, the writer implements the results of the research into the Information System Design of Lecturer Journal in the Study Program at the PTI Faculty of Teacher Training and Education, Unimuda Sorong.